Menilai Perkembangan Motorik Kasar Anak Melalui Permainan Lompat Tali - Ferasinta Ferasinta; Padila Padila; Rahma Anggita (Jurnal Kesmas Asclepius, 2022)
This study aims to determine the effect of rope jumping games on gross motor skills in children. This study uses a Quasy Experiment research design with a One Group Pre-Post Design approach. The results of this study show the effect of jumping rope on gross motor development in children with pre-test and post-test data of jumping rope with p-value = 0.001. In conclusion, rope jumping games affect gross motor development in children because rope jumping games have jumping movements in a balanced and coordinated manner. Keywords: Jumping Rope, Jumping, Gross Motor